Worlds Ending. Ending Worlds : Understanding Apocalyptic Transformation - Jenny Stümer; Michael Dunn (De Gruyter Oldenbourg, 2023)
The notion of apocalypse is an age-old concept which has gained renewed interest in popular and scholarly discourse. The book highlights the versatile explications of apocalypse today, demonstrating that apocalyptic transformations – the various encounters with anthropogenic climate change, nuclear violence, polarized politics, colonial assault, and capitalist extractivism – navigate a range of interdisciplinary views on the present moment. Moving from old worlds to new worlds, from world-ending experiences to apocalyptic imaginaries and, finally, from authoritarianism to activism and advocacy, the contributions begin to map the emerging field of Apocalyptic and Post-Apocalyptic Studies. Foregrounding the myriad ways in which collective imaginations of apocalypse underpin ethical, political, and, sometimes, individual experience, the authors provide key points of reference for understanding old and new predicaments that are transforming our many worlds.